PANDANGAN MASYARAKAT DESA TERHADAP SEKOLAH BERBASIS AGAMA (STADI KASUS DI DESA DAMES DAMAI KECAMATN SURALAGA) - Muh. Taqiudin (Universitas Hamzanwadi, 2020)
School is an institution that plays a role in the field of education. School is the second educational institution after the family therefore the school is very important in supporting the knowledge of society. So in this educational institution there are aspects of aspects that must be understood that includes, awareness or knowledge and actions utuk melaksanakam values, both to the one God, self, fellow, environment and kebangsan sehigga be human human kamil. This research aims to know the views of the village community against religious schools in Dames Damai Village. In conducting this researcher, the writer uses the method in the case of the meaning of data collected in a case, studied as a whole in entegeration, whose purpose is to deepen the knowledge of the object in the perusal. There is also obuek in the intention is the view of society towards religious schools in the village Dames Damai suralaga district. In the use of methods after case the author collaborated with the deskeriftif approach. The descriptive approach used in this research is qualitative descriptive approach. People's views on religion-based schools are very strong even when faced with perograms from public schools their belief in religious schools will never change, this belief is none other than because society sees objectively because religious schools prove that programs runs, applied policies, ongoing rules and religious activities. All these perograms are run and enjoyed by the community through all religious sympathizers of schools.